2005
DOI: 10.1111/j.1532-5415.2005.53415.x
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Hypotension Predicts All‐Cause Mortality in Older, Low‐Level Care Residents

Abstract: In older low-level-care residents, PPH is an independent predictor of all-cause mortality with no added predictive value explained by other BP indices: OH, hypertension, PP, MAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 43 publications
2
98
6
1
Order By: Relevance
“…Phase 3 studies focusing on the blood-glucose-lowering effects of GLP-1 agonists indicate durable, modest reductions in systolic and, less consistently, diastolic blood pressure (BP), and a slight rise in heart rate (HR) [4][5][6][7]. Postprandial hypotension (PPH), defined as a fall in systolic BP ≥20 mmHg within 2 h of a meal [8], is a common disorder, associated with substantial morbidity and increased mortality [9], for which current management is suboptimal [10]. Groups most affected are older individuals, particularly those in residential care, and patients with autonomic dysfunction, including those with diabetes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Phase 3 studies focusing on the blood-glucose-lowering effects of GLP-1 agonists indicate durable, modest reductions in systolic and, less consistently, diastolic blood pressure (BP), and a slight rise in heart rate (HR) [4][5][6][7]. Postprandial hypotension (PPH), defined as a fall in systolic BP ≥20 mmHg within 2 h of a meal [8], is a common disorder, associated with substantial morbidity and increased mortality [9], for which current management is suboptimal [10]. Groups most affected are older individuals, particularly those in residential care, and patients with autonomic dysfunction, including those with diabetes [10].…”
Section: Introductionmentioning
confidence: 99%
“…Postprandial hypotension (decreased systolic blood pressure ≥20 mmHg or in systolic blood pressure <90 mmHg when previously ≥100 mmHg within 2 hours after meal) is common in institutionalized older adults (>75 years old) 1,4 contributing to syncope, falls, cardiac events/ stroke, and increased mortality [2][3][4][5][6][7][8] . Proposed mechanisms include blunted gastrovascular sympathetic reflex post-meal 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence in institutionalized elders has been estimated at 25%-38% [17] although a study in Holland reported a prevalence of 67% amongst geriatric patients [44]. One study concluded that "in older low-level-care residents, postprandial hypotension is an independent predictor of all-cause mortality with no added predictive value explained by other blood pressure indices: orthostatic hypotension, hypertension, pulse pressure or mean arterial pressure" [18]. As Artemisia absinthium and Gentiana lutea increase vascular peripheral resistance, which acts to increase blood pressure and reduce cardiac workload they have the potential to reduce the burden of postprandial hypotension.…”
Section: Gastroparesismentioning
confidence: 99%
“…Postprandial hypotension is defined as a drop in systolic pressure of ≥ 20 mmHg, or a decrease below 90 mmHg, within 2 hours of eating. Postprandial hypotension can result in falls, syncope, coronary events and strokes [17] and it is associated with both coronary events and overall mortality [18,19] …”
Section: Oropharyngeal Taste Physiologymentioning
confidence: 99%